RICOSRE: A Learning Model to Develop Critical Thinking Skills for Students with Different Academic Abilities - Mahanal, Susriyati; Zubaidah, Siti; Sumiati, Ika Dewi; Sari, Tri Maniarta; Ismirawati, Nur (International Journal of Instruction, 2019)
The purpose of this study was to investigate the effect of RICOSRE learning models towards critical thinking skills of students with different academic abilities. This quasi-experimental study employed a pretest-posttest nonequivalent control group design and involved all the eleventh-grade students from high schools in Malang, Indonesia. The sample consisted of 134 students from two separate schools which represented different academic abilities (high and low). Data were collected using an essay test on students' critical thinking skills. A rubric was employed to assess students' answers and the results were analyzed using ANCOVA. Findings suggest that (1) there is a difference between the critical thinking skills of students whose learning was facilitated with RICOSRE and critical thinking skills of students who were engaged in conventional learning, (2) there is a critical thinking difference between the high and low ability students, (3) there is a difference in students' critical thinking skills affected by the interaction between learning models and students' academic abilities. Based on the results of this study, it can be concluded that RICOSRE can close the critical thinking skills gap between the high and low ability students.